Draft Annual Plan, 2008-2009 Maharashtra State Part I - Planning Commission (Planning Commission, 2008)
The priorities as determined by the National Development Council (NDC) in December 2006 for the Eleventh Five Year Plan and accordingly sufficient outlay has been provided in the Annual Plan 2008-2009. Priorities of the Annual Plan 2008-2009 Growth rate of 9% in GDP. Development in infrastructure Project on BOT basis so as to release Government funds for social sector. Work for improving health standard, nutrition standard, education and economic well being of people with a view to bring down the population growth rate. Vigorous implementation of programmes for improving socio economic indicators like National Rural Health Mission (NRHM), Sarva Shiksha Abhiyan, NR-EGS, Bharat Nirman, JN-NURM, BRGF, ARWSP.
Planning Department Government of Maharashtra